Spectrum of Morphological Changes and Prevalence of “P53 Signatures” in Tubal Fimbrial Epithelium in General Population and in Patients with Pelvic Serous Carcinomas - Ravikumar, Gayatri; Crasta, Julian (Cancers Review, 2015)
Aim: Pelvic serous carcinomas (PSCs) are very aggressive malignancies and present at advanced stage. A paradigm shift in the origin and pathogenesis of PSCs occurred when precursor lesions were found in the Fallopian tube fimbria in the prophylactic bilateral salphingo-ophorectomy (PBSO) specimens from BRCA positive patients. The knowledge of various benign and reactive alterations in the Fallopian tube is mandatory to distinguish these lesions from the true neoplastic changes. The study therefore aims to see the spectrum of morphological changes in the Fallopian tube epithelium (FTE) and to know the incidence of the various precursor lesions and p53 signatures in the tubal fimbria. Method: The study included 102 Fallopian tubes from patients undergoing salphingo – oophorectomies for gynaecological indications. The fimbrial end along with one cross section was embedded and examined for stromal and architectural changes, epithelial features and inflammatory infiltrates. IHC for p53 and Ki67 was done to assess the presence of precursor lesions. Results: The mean age of patients’ was 49.9yrs. Family history of breast/ovarian cancer was present in 5 cases. Histopathology showed fibrosis (30%), Walthard nest (36%) , Wolfian duct remnants(14.7%), pigmentosis tubae(1%) , infiltration by metastatic carcinoma(7%),reactive atypia(6%), metaplasia(16%), tufting(46%),lymphocytes (9%) and plasma cells (2%). SCOUTS were seen in 12%, p53 signature and STIC in 6% and 4% respectively. Tuboperitoneal junction was identified in 15 cases and showed transitional metaplasia. Conclusion: The study describes the different morphological changes in the Fallopian tube in our population. The prevalence of cytological and molecular alterations leading to malignancy was low in general population.